(untitled) (Педагогіка вищої та середньої школи, 2006)
Psychological nature of aesthetically beautiful necessity is examined in the article, its rich (realized) in content and functional (unrealized) even, related to the ways of receipt of aesthetically beautiful information: the features of psihofiziologichnogo mechanism (functional organa) of necessity. which setting to activity of certain direction is on the base of open up.